Preventing medication errors - Aspden, Philip (Quality chasm series., 2007)
"Preventing Medication Errors begins by providing an overview of the system for drug development, regulation, distribution, and use. It also examines the peer-reviewed literature on the incidence and the cost of medication errors and the effectiveness of error prevention strategies. Presenting data that will foster the reduction of medication errors, the book provides action agendas detailing the measures needed to improve the safety of medication use in both the short- and long-term. Patients, primary health care providers, health care organizations, purchasers of group health care, legislators, and those affiliated with providing medications and medication-related products and services will benefit from this guide to reducing medication errors."--Jacket.